Investigation on the Deterioration Mechanism of Recycled Plaster - Zhixin Li; Kaidong Xu; Jiahui Peng; Jina Wang; Xianwei Ma; Jishou Niu (Advances in Materials Science and Engineering)
The deterioration mechanism of recycled plaster (R-P) was studied. The large specific surface area (SSA), improper preparation temperature, increased water requirement of R-P, and microstructure of its hardened body were analyzed by particle size distribution (PSD), Blaine method, differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and nitrogen adsorption porosimetry. The results indicated that the properties of R-P were deteriorated, but its strength decreases from 50% at the same manufacturing process to 30%–40% at similar specific surface area. The analysis shows that the large SSA, poor morphology, narrow PSD, and increased internal detects give rise to increase of water requirement. In addition, the deterioration properties are caused by unsuitable temperature of preparation, loose structure, and large average pore diameter in hardened R-P as well.